Changes in the prevalence of fungal species causing post-harvest diseases of carrot in Finland - Latvala, Satu; Haapalainen, Minna; Karisto, Petteri; Kivijärvi, Pirjo; Jääskeläinen, Oona; Suojala‐Ahlfors, Terhi (John Wiley & Sons, 2024)
Post-harvest diseases cause significant economic losses in the carrot productionchain. In this study, storage losses and fungal pathogens causing them were analysedin the carrot yield from 52 different field plots in four areas in Finland in 3 years(2016–2018). Over 30,000 carrots were sampled and analysed at three time pointsduring cold storage at 0–1 C. In March, after 5–6 months' storage, the average lossdue to diseases was 20%–21% every year. Decay of the root tip was the most com-mon disease symptom, followed by pits on the side and black rot in the crown,detected in 69.2%, 15.0% and 9.0% of the symptomatic samples, respectively. Bothintensive carrot cultivation practice and early timing of harvest increased storagelosses. Pathogens in 3057 symptomatic carrot tissue samples were isolated by cultur-ing, and fungal species were identified. The most common fungal species detectedwereMycocentrospora acerina,Botrytis cinereaandFusariumspp., especiallyF. avenaceum. However, the frequency of different pathogens varied between thedifferent years and time points during storage. Species-specific PCR tests revealedthatM. acerinaandF. avenaceumwere present in many early time-point sampleswhere they could not yet be detected by the culturing method. In Finland, this studyon carrot post-harvest diseases is the first large-scale survey in which the fungalpathogens were isolated and identified by laboratory tests. In comparison with theprevious studies,Fusariumspp. were detected more frequently in this study, whilegrey mould and Sclerotinia rot were less frequent.
Keywords: crop rotation; culturing method; Daucus carota; fungal diseases; Fusarium; harvest time; PCR